Bounded generalized random linear operators - Nguyen, Thinh (VNU Journal of Science: Mathematics - Physics; Vol 33 No 3, 2017)
In this paper we are concerned with bounded generalized random linear operators. It is shown that each bounded generalized random linear operator can be seen as a set-valued random variable. The properties of some special bounded generalized random linear operators are given also. As an application the notion of random resolvent set of a generalized random linear operator is introduced and investigated.